CompTIA Project+ Study Guide Exam PK0-005. - Heldman, Kim (John Wiley & Sons, Incorporated, 2022)
Prepare for the Project+ exam and a new career in project management quickly and efficiently with a newly updated guide In the newly revised Third Edition of the CompTIA Project+ Study Guide: Exam PK0-005, veteran project manager and tech educator Kim Heldman delivers a fully updated and comprehensive guide to the foundational CompTIA Project+ exam. This all-in-one study aid focuses on the job-critical skills demanded by employers and will help you hit the ground running on your first day in a new project management role. In this Study Guide, you'll learn to manage the project lifecycle, coordinate small- and medium-sized projects, establish communication plans, manage resources and stakeholders, maintain project documentation and artifacts, and support the completion of larger projects within an information technology environment. It also offers: Hands-on, concrete guidance designed to banish test anxiety and prepare you for the entry-level CompTIA Project+ exam Detailed advice on project management concepts, lifecycle phases, project tools and documentation, and IT and governance basics required by on-the-job project managers Complimentary access to Sybex's interactive, online learning environment and test bank, complete with an assessment test, hundreds of practice questions, practice exams, electronic flashcards, and a searchable glossary of key terms Full of practical examples and insights drawn from the author's extensive, real-world experience, the newest edition of CompTIA Project+ Study Guide: Exam PK0-005, Third Edition, is a must-read for anyone considering a new career in project management or preparing for the CompTIA Project+ exam.